Perhitungan Konsumsi Obat Untuk Logistik Medik di Rumah Sakit Islam Jemursari Surabaya - Nur Azizah Fairuz; Tito Yustiawan (Universitas Airlangga, 2017)
Inaccurate drugs planning may cause excessive budget, stagnant, and stockout. This research aims to analyze drugs planning in medical logistics of Rumah Sakit Islam Jemursari Surabaya. This research is a descriptive study using cross sectional design. Primary data were obtained through observations and interviews. Secondary data were obtained through drugs planning and drugs consumption data from November to December 2016. Afterward, data were processed and found that 40% drugs item on November 2016 have greater amount of consumption than their planning and 65% drugs item on December 2016 have greater amount of consumption than their planning. The method of drugs planning that used in medical logistics of Rumah Sakit Islam Jemursari Surabaya was consumption method, but it was not calculate the average of drugs consumption. After the calculation based on Keputusan Menteri Kesehatan Nomor 1121 Tahun 2008, there is only 20% drugs item on November 2016 which have greater amount of consumption than their planning and 20% drugs item on December 2016 which have greater amount of consumption than their planning. This research showed that the calculation of drugs consumption for medical logistics in Rumah Sakit Islam Jemursari Surabaya need repairement.Keywords: consumption method, drugs planning, hospital